2016
DOI: 10.1631/jzus.b1600257
|View full text |Cite
|
Sign up to set email alerts
|

Developing a rat model of dilated cardiomyopathy with improved survival

Abstract: To compare the continuous infusion and intermittent bolus injection administration protocols of doxorubicin (Dox) under the same cumulative dose (12 mg/kg), and establish a rat dilated cardiomyopathy model with improved survival, a total of 150 Sprague-Dawley (SD) rats were divided into three groups: a control group, administered with normal saline; a Dox 1 group, administration twice a week at 1 mg/kg; a Dox 2, administration once a week at 2 mg/kg. Mortality rates in the Dox 1 and Dox 2 groups were 22% and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
1
12
1
Order By: Relevance
“…The procedures were as follows: rats were intraperitoneally injected with 2.5 mg/kg Doxorubicin once per week for 10 weeks. Transthoracic echocardiography and haemodynamic monitoring were performed to verify whether the rat model with DCM was constructed successfully . After successful establishment of the rat model with DCM, the 50 rats were randomly assigned into a DCM (no treatment), DCM + negative control (NC) (DCM rats injected with 5 µL of LTBP2 negative control siRNA sequence), DCM + si‐LTBP2 (DCM rats injected with 5 µL of si‐LTBP2‐treated cell suspension (20 ng/ml) with a cell concentration of 1 × 10), DCM + PMA (activator of the NF‐κB signalling pathway) (DCM rats injected with 5 µL of PMA‐treated cell suspension (1 µmol/L) at a cell concentration of 1 × 10 5 ) and DCM + si‐LTBP2 + PMA (DCM rats injected with 5 µL of a mixture treated with si‐LTBP2 and PMA (20 ng/mL) groups.…”
Section: Methodsmentioning
confidence: 99%
“…The procedures were as follows: rats were intraperitoneally injected with 2.5 mg/kg Doxorubicin once per week for 10 weeks. Transthoracic echocardiography and haemodynamic monitoring were performed to verify whether the rat model with DCM was constructed successfully . After successful establishment of the rat model with DCM, the 50 rats were randomly assigned into a DCM (no treatment), DCM + negative control (NC) (DCM rats injected with 5 µL of LTBP2 negative control siRNA sequence), DCM + si‐LTBP2 (DCM rats injected with 5 µL of si‐LTBP2‐treated cell suspension (20 ng/ml) with a cell concentration of 1 × 10), DCM + PMA (activator of the NF‐κB signalling pathway) (DCM rats injected with 5 µL of PMA‐treated cell suspension (1 µmol/L) at a cell concentration of 1 × 10 5 ) and DCM + si‐LTBP2 + PMA (DCM rats injected with 5 µL of a mixture treated with si‐LTBP2 and PMA (20 ng/mL) groups.…”
Section: Methodsmentioning
confidence: 99%
“…On the 8th day, DCM models were established in the combination drug group, trimetazidine group and control group rats (23). Adriamycin was injected intraperitoneally at a dose of 1 mg/kg twice per week for 6 weeks.…”
Section: Establishment Of Dcm Rat Modelmentioning
confidence: 99%
“…These results are in agreement with other research which indicated that caspase-3 activation is elevated during DXR-induced heart failure. 25 28 Moreover, melatonin protected the heart from myocardial ischemia by down regulating the cleaved caspase-3 expression in this rat model. 28,29…”
Section: Antracyclinesmentioning
confidence: 72%